Strange new spiders: on Roddenberryus, a new and unusual caponiid genus (Araneae, Caponiidae) - Sánchez-Ruiz, Alexander; Bonaldo, Alexandre B. (European Journal of Taxonomy, 2023)
The new nopine genus Roddenberryus gen. nov. is erected to include in total five species: three new species, R. kirk gen. et sp. nov. (male and female) from Costa Rica, R. spock gen. et sp. nov. (female) from Campeche, Mexico and R. mccoy gen. et sp. nov. (male) from Baja California Sur, Mexico, as well as two species previously misplaced in Caponina Simon, i.e., R. sargi (Pickard-Cambridge, 1899) gen. et comb. nov. from Guatemala and R. pelegrina (Bryant, 1940) gen. et comb. nov. from Cuba. A male specimen reported as C. sargi Pickard-Cambridge from Costa Rica by E. Kritscher (1957) is assigned to Roddenberryus kirk together with one female collected at the same locality. The new genus is characterized by the distally projected endites and a triangular, projected labium, a conformation unique among nopines; also by a triangular, very short, scaly gladius, serrula with interspersed multiple tooth rows, and a tarsal organ with strongly projected margins. Roddenberryus shares with Tarsonops Chamberlin the cracked tarsi and metatarsi, with multiple adesmatic joints intertwined on the cuticle and an unusual internal respiratory system with both posterior tracheae fused in a single trunk.